Pengaruh Psikoedukasi Audio Visual Berbasis Implementation Intention Terhadap Niat dan Perilaku Kepatuhan Minum Obat Pasien Tuberkulosis (TB) di Wilayah Kerja Dinas Kesehatan Kabupaten Tulungagung - Anita Dewi Anggraini; Soedarsono Soedarsono; Laily Hidayati (Jurnal Penelitian Kesehatan SUARA FORIKES, 2019)
Introduction: Treatment failure, disease transmission and drug resistance were problems that occur due to non-compliance. One of the factors caused non-compliance was a prolonged psychological problem and a lack of patient commitment to treatment. Psychoeducation which was guided by implementation intention and packaged in audio-visual form was expected to improve intention and medication adherence behaviour. Aims: This study aims to explain the effect of implementation intention based audiovisual psychoeducation on intention and taking medicine adherence behaviour of TB patients in the Tulungagung District Health Office. Methods: The research method used was a quasi-experimental design with a pre-post control group. The study sample was 72 TB patients who underwent intensive category 1 treatment as many as 2 divided into 2 intervention groups (n=36) and controls (n=36). Samples were taken by cluster random sampling, inclusion criteria for intensive treatment category 1 TB patients (1-2 months), aged 18-65 years and able to communicate verbally and in writing well. The intention of taking medicine was assessed using a questionnaire about intentions developed from Sari et all research, while taking medicine adhererence behaviour was assessed using the Morisky Medication Adherence Scale (MMAS-8) questionnaire which has been developed by Mahayu et al. Data was analyzed using the Wilcoxon-marked ranking test and Mann-Whitney test. Results: After audio visual psychoeducation intervention based on implementation intention, it was found that there was a significant increase in intetion and taking medicine adherence behaviour in the intervention group with P